Ultrasound detection of diaphragm position in the region for lung monitoring by electrical impedance tomography during laparoscopy - Buzková, Kristýna; Müller, Martin; Rára, Aleš; Roubík, Karel; Tyll, Tomáš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2018)
BACKGROUND AND AIMS: During laparoscopic surgery, a capnoperitoneum is created to optimize the operating space for surgeons. One effect of this is abdominal pressure which alters the physiological thoraco-abdominal configuration and pushes the diaphragm and lungs cranially. Since the lung image acquired by electrical impedance tomography (EIT) depends on the conditions within the thorax and abdomen, it is crucial to know the diaphragm position to determine the effect of diaphragm shift on EIT thorax image. METHODS: The presence of diaphragm in the region of EIT measurement was determined by ultrasound in 20 patients undergoing laparoscopic surgery. Data were obtained in the supine position during spontaneous breathing in a mechanically ventilated patient under general anesthesia with muscle relaxation and in a mechanically ventilated patient under general anesthesia with muscle relaxation during capnoperitoneum. RESULTS: The diaphragm was shifted cranially during capnoperitoneum. The diaphragm detection rate rose by 10% during capnoperitoneum at the fifth intercostal space, from 55% to 65% and by 10% from 0% at mid-sternal level compared to mechanical ventilation without capnoperitoneum. CONCLUSION: The diaphragm was detected in the area contributing to the creation of the thoracic EIT image. Considering the cranial shift of diaphragm caused by excessive intra-abdominal pressure, the impedance changes in the abdomen and the principle of EIT, we assume there could be a significant impact on EIT image of the thorax acquired during capnoperitoneum. For this reason, for lung monitoring using EIT during capnoperitoneum, the manufacturer's recommendation for electrode belt position is not appropriate. The study was registered in ClinicalTrials.gov with an identifier NCT03038061.
Keywords: počítačová rentgenová tomografie; Humans; laparoskopie; Pneumoperitoneum, Artificial; lidé středního věku; ventilace umělá s výdechovým přetlakem; Positive-Pressure Respiration; Thorax; hrudník; Female; Aged; Lung; pneumoperitoneum umělé; senioři; lidé; plíce; reprodukovatelnost výsledků; ženské pohlaví; Male; Reproducibility of Results; Middle Aged; Tomography, X-Ray Computed; bránice; Laparoscopy; Diaphragm; elektrická impedance; mužské pohlaví; prospektivní studie; Electric Impedance; Prospective Studies